Control strategies for Madeira vine (Anredera cordifolia) - Webb, H.J.; Harrington, K.C. (New Zealand Plant Protection, 2005)
Madeira vine is an environmental weed with both aerial and subterranean tubers and is listed as a Surveillance Plant Pest by ManawatuWanganui Regional Council A field trial showed mature vines and their attached tubers were best controlled using metsulfuronmethyl although reasonable control was also provided by a triclopyr/picloram mixture and by glyphosate The control of regrowth from buried tubers was investigated in a glasshouse trial Herbicides that gave good control of 3monthold plants included the above herbicides and also tribenuronmethyl fluroxypyr and amitrole For eradication purposes treatments were assessed for destroying aerial tubers collected from isolated plants Tubers were killed by freezing by heating to temperatures of 80C or above for 24 h or by boiling for a few minutes but any pulverisation techniques needed to be thorough Tubers immersed momentarily in high concentrations of picloram triclopyr or fluroxypyr did not regrow after burial